DNA methylation of miR-138 regulates cell proliferation and EMT in cervical cancer by targeting EZH2 - Rui Chen; Qiyu Gan; Shuting Zhao; Dongrui Zhang; Shunli Wang; Lili Yao; Min Yuan; Jingxin Cheng (BMC Cancer, 2022)
Abstract Background Emerging evidence has identified miR-138 as a tumor suppressor that can suppress the proliferation of various cancers. Meanwhile, the cause of abnormal miR-138 expression in cervical cancer remains uncertain. This study clarified the mechanism by which miR-138 regulates proliferation, invasion, metastasis, and EMT in cervical cancer cells. Results miR-138 expression in human cervical cancer and adjacent normal tissue was measured using qPCR. SiHa and C33A cells were used to determine the function of miR-138 via miR-138 mimic or inhibitor transfection, followed by wound healing, Cell Counting Kit-8, flow cytometry, and Transwell assays. Epithelial and mesenchymal marker expression was analyzed using Western blotting. DNA methylation in the miR-138 promoter was examined using bisulfite sequencing PCR. The downstream target genes of miR-138 were identified via bioinformatics analysis and luciferase reporter assays. A tumor xenograft model was employed to validate DNA methylation-induced miR-138 downregulation and tumor growth inhibition in cervical cancer in vivo. miR-138 levels were significantly lower in cervical cancer tissues than in adjacent control tissues. Furthermore, lower miR-138 expression and higher CpG methylation in the miR-138 promoter were identified in lymph node-positive metastatic cervical cancer tumors versus that in non-metastatic tumor tissues. Upon miR-138 overexpression, cell proliferation, metastasis, invasion, and EMT were suppressed. miR-138 agomir transfection and demethylating drug treatment significantly inhibited cervical tumor growth and EMT in tumor xenograft models. DNA methylation inhibited miR-138 transcription, and enhancer of zeste homolog 2 (EZH2) downregulation mediated the tumor suppressor function of miR-138 in cervical cancer. Conclusion We demonstrated that miR-138 suppresses tumor progression by targeting EZH2 in cervical cancer and uncovered the role of DNA methylation in the miR-138 promoter in its downregulation. These findings demonstrated the potential of miR-138 to predict disease metastasis and/or function as a therapeutic target in cervical cancer.